Effect of pregnancy induced hypertension on pregnancy outcome: a hospital based cross sectional study at a tertiary care hospital - Bindu, K. Hima; Devi, E. Rama (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: I Pregnancy induced hypertension causes intra uterine growth retardation, pre-mature delivery, intra uterine death of fetus, abruption placentae. It also causes increased morbidity and mortality among women. The objective of the present study is to observe the effect of pregnancy induced hypertension on pregnancy outcome. Methods: A hospital based cross sectional study was carried out to study the effect of pregnancy induced hypertension on pregnancy outcome for a period of two years from April 2004 to March 2006 at Gandhi Medical College, Hyderabad. Results: The mean maternal age in group I was 22.9 years comparable to group II. The incidence of PIH was 10.7% among primipara compared to 9.1% among multi parous women. Mean gestational age at entry to the present study was comparable among both the groups. Mean gestational age at delivery was higher in normotensive women compared to women with PIH. The incidence of low birth weight was 70% among PIH group compared to only 16.7% in normotensive group and this difference was found to be statistically significant. The incidence of intra-uterine growth retardation (IUGR) was 70% among PIH group compared to only 16.7% in normotensive group and this difference was found to be statistically significant. The incidence of pre-term delivery was 70% among PIH group compared to only 16.7% in normotensive group and this difference was found to be statistically significant. Conclusions: T Pregnancy induced hypertension was positively associated with adverse outcome. Early diagnosis and proper management can help to overcome and tackle most of the adverse outcomes.